Evaluation of Antibiotic Use in Pediatric Inpatients at one of Bandung Regional Hospitals in August 2023 - Maharani, Putri; Wicaksono, Imam A.; Puspita, Falerina; Zainudin, Hijrah M. (Pharmacology and Clinical Pharmacy Research, 2024)
Infectious diseases are a major concern in the field of health, especially in developing countries like Indonesia. Children are vulnerable to infections because their immune systems are not fully developed. Proper management is necessary for the prevention and treatment of infectious diseases in pediatric patients. Antibiotics are the primary choice for addressing bacterial infections. However, the increased use of antibiotic can contribute to high levels of antimicrobial resistance (AMR), rendering infection treatment ineffective. The evaluation of antibiotic use can be conducted through the ATC/DDD method, which focuses on the quantity and types of antibiotics used. Although this method provides a quantitative overview, a qualitative approach using the Gyssens method and interviews with relevant parties is necessary for a more in-depth understanding of the rationality of antibiotic use. This study aims to comprehend the patterns of antibiotic use in pediatric inpatients at one of Bandung Regional Hospitals during August 2023. Using a retrospective observational approach, data were collected and processed using the ATC/DDD method. The evaluation results show that cephalosporins is the most commonly used antibiotic group, with cefotaxime being the dominant antibiotic administered intravenously. Quantitative evaluation indicates variations in DDD/100 patient days among different antibiotics, with ciprofloxacin having the highest value and amikacin the lowest. For a comprehensive understanding, qualitative research using the Gyssens method and interviews is necessary to strengthen the evaluation results of antibiotic use. Ultimately, this study provides a thorough perspective on antibiotic use in pediatric inpatients, supporting efforts to control antimicrobial resistance and promote more judicious antibiotic selection.